Implementation of Heuristic Silver Meal Method in Planning and Control Scrap Supplies in Growth Sumatra Industry Company - Parinduri, Luthfi; Hasibuan, Abdurrozzaq; Arfah, Mahrani; Krianto Sulaiman, Oris; Yudianto, Y (International Journal of Engineering and Technology, 2026)
The raw materials used in the form of scrap are obtained from local suppliers and importers. In the management of scrap so far still apply traditional patterns that have not been scientific. This condition is actually less profitable for companies in market conditions and competition is increasingly competitive. To ensure the smooth process and optimization of production in this study Implementation of Heuristic Silver Meal Method in Planning and Control Scrap Supplies. Selection of this method is based on From the research result obtained safety stock for local scrap as much as 306 Ton/Month, while for imported scrap as much as 186 ton/month. Based on the calculation of lot size using heuristic silver-meal method in obtaining a lot of 12 bookings for local scrap as well as time of re-ordering of raw materials (reorder point) of 399 Ton. While for scrap import 6 times the order and reorder (reorder point) of 267 Ton. With the application of this method obtained savings of Rp. 496.560.000 in 2018, a significant amount.
Keywords: Safety stock; Heuristic Silver-Meal; reorder point